Requirements for driving antipathogen effector genes into populations of disease vectors by homing. - Beaghton, A; Hammond, A; Nolan, T; Crisanti, A; Godfray, H; Burt, A (Genetics Society of America, 2017)
There is a need for new interventions against the ongoing burden of vector-borne diseases such as malaria and dengue. One suggestion has been to develop genes encoding effector molecules that block parasite development within the vector, and then use the nuclease-based homing reaction as a form of gene drive to spread those genes through target populations. If the effector gene reduces the fitness of the mosquito and does not contribute to the drive, then loss-of-function mutations in the effector will eventually replace functional copies, but protection may nonetheless persist sufficiently long to provide a public health benefit. Here, we present a quantitative model allowing one to predict the duration of protection as a function of the probabilities of different molecular processes during the homing reaction, various fitness effects, and the efficacy of the effector in blocking transmission. Factors that increase the duration of protection include reducing the frequency of pre-existing resistant alleles, the probability of nonrecombinational DNA repair, the probability of homing-associated loss of the effector, the fitness costs of the nuclease and effector, and the completeness of parasite blocking. For target species that extend over an area much larger than the typical dispersal distance, the duration of protection is expected to be highest at the release site, and decrease away from there, eventually falling to zero, as effector-less drive constructs replace effector-containing ones. We also model an alternative strategy of using the nuclease to target an essential gene, and then linking the effector to a sequence that restores the essential function and is resistant to the nuclease. Depending upon parameter values, this approach can prolong the duration of protection. Our models highlight the key design criteria needed to achieve a desired level of public health benefit.